A novel peripheral cannabinoid 1 receptor antagonist, AJ5012, improves metabolic outcomes and suppresses adipose tissue inflammation in obese mice - Han, Ji Hye; Shin, Hanho; Park, Ju Young; Rho, Jun Gi; Son, Dong Hwee; Kim, Ki Woo; Seong, Je Kyung; Yoon, Sung Hwa; Kim, Wook (FASEB Journal, 2019)
The overactivity of cannabinoid 1 receptor (CB1R) is associated with obesity and type 2 diabetes. First-generation CB1R antagonists, such as rimonabant, offered therapeutic advantages for the control of obesity and related metabolic abnormalities, but their therapeutic potential was limited by undesirable neuropsychiatrie side effects. Here, we evaluated AJ5012 as a novel potent peripheral CB1R antagonist and, using this antagonist, investigated the role of peripheral CB1R on adipose tissue inflammation in obese mouse models. AJ5012 had a high degree of CB1R and cannabinoid 2 receptor selectivity but a low brain:plasma concentration ratio without eliciting centrally mediated neurobehavioral effects. In diet-induced obese (DIO) mice, AJ5012 did not reduce food intake but did induce a significant weight loss, likely owing to an increased energy expenditure. It was as effective as rimonabant for the improvement of hormonal or metabolic abnormalities, glycemic control, and insulin sensitivity. The treatment of DIO and leptin receptor–deficient mice with AJ5012 also exhibited effects comparable to rimonabant for the prevention of macrophage infiltration, activation of the nucleotide-binding domain and leucine-rich repeat protein 3 inflammasome, and production of proinflammatory cytokines, which resulted in the suppression of adipose tissue inflammation. In addition to macrophage, activation of CB1R in 3T3-L1 adipocytes induced the expression of proinflammatory genes, which was fully inhibited by AJ5012. Our findings identified AJ5012 as a novel peripheral CB1R antagonist and suggest that peripheral CB1R blockade might break the links between insulin resistance and adipose tissue inflammation.—Han, J. H., Shin, H., Park, J.-Y., Rho, J. G., Son, D. H., Kim, K. W., Seong, J. K., Yoon, S.-H., Kim, W. A novel peripheral cannabinoid 1 receptor antagonist, AJ5012, improves metabolic outcomes and suppresses adipose tissue inflammation in obese mice. FASEB J. 33, 4314–4326 (2019). www.fasebj.org.
Keywords: 3T3 Cells; Adipose Tissue; Animals; CHO Cells; Cricetulus; Cytokines; Diabetes Mellitus, Type 2; Energy Metabolism; Female; Humans; Hypoglycemic Agents; Inflammasomes; Inflammation; Insulin Resistance; Macrophages; Male; Mice; Mice, Inbred C57BL; Mice, Obese; Obesity; RAW 264.7 Cells; Receptor, Cannabinoid, CB1; Receptor, Cannabinoid, CB2; Rimonabant; Weight Loss; cannabinoid receptor; CB1R antagonist; inflammation; insulin resistance; obesity